ANALYSIS OF DEBT SHORT TERM AND RECEIVABLE TURNOVER ON THE PROFITABILITY OF MANUFACTURING COMPANIES - Dian Efriyenty (Khazanah Multidisiplin, 2020)
ABSTRACTBased on the survey results for the last 3 years, data on food companies and the minimum turnover of accounts receivable and debt has increased and this has an impact on taking profits in the form of assets. These things can have an impact on the investment invested in shareholders. The purpose of this study is to assess the effect of short-term debt and accounts receivable turnover on asset returns. The samples in this study were 8 companies in the 2015-2019 period. The results of t-test analysis partially show that short-term debt does not have a significant effect on profitability, receivables turnover has a significant effect on profitability.Â Keywords: short-term debt, accounts receivable turnover, profitability